Diag-AID: a diagnostic aid for medical image enhancement using colour coding and modified histogram equalisation techniques. (10th October 2011) - Prasad, Keerthana; Prabhu, G.K.
Diag-AID, a generic and interactive tool for enhancement of a medical image was developed to facilitate easy diagnosis. Two techniques namely colour coding and contrast enhancement through modified histogram equalisation were used. This tool was designed to provide a way of saving the image with the region of interest encoded into it in such a way that the saved image could be viewed as a greyscale image or a colour coded image or greyscale image with the region of interest highlighted. The HSI colour space was used for designing a look-up table (LUT) for colour coding. The original image information was coded into the colour components read from the LUT using the least significant bit watermarking technique. Diag-AID acts as a diagnostic aid by facilitating medical image enhancement and documentation of the expert's interpretation.